Technology for the production of cottonseed oil (Research, Society and Development, 2023)
The verticalization of the cotton crude oil by-product may be the goal of some cotton companies that have, besides the ginning and hydraulic press machines for fiber baling, an oil extraction unit, but that needs to add to their production circuit, agroindustrial refining processes for the production of edible oil. Therefore, this work aims to show ways that can improve the procedures of cottonseed preparation, almond oil extraction and oil refinement, highlighting in each stage of the processes involved from the arrival of raw cotton in the agroindustry until the output of the final products. To be successful in such an undertaking it is necessary to improve the product marketing (refined oil) because the cottonseed has adequate protein characteristics, which enables its use in the food industry. In addition, this value addition of crude cotton oil will depend on the acquisition of some equipment required in its refinement processes and also on the initial quality of the seed, when freshly harvested and with humidity around 10%, determine the obtaining of a good oil.